Islam’s encounter with women’s rights and feminism: the need for greater engagement of Muslim women - Hasan, Md. Mahmudul (Bangladesh Institute of Islamic Thought (BIIT), Dhaka, 2013)
The question of women‘s rights in Islam generates huge interest among Muslims and non-Muslims alike. Scholars of feminism are sharply divided on the question of women‘s status in Islam. One group associates Islam with misogyny and gender oppression, while the other celebrates the religion as a liberatory force for women. Remarkably, despite a surge in female educational attainment and consciousness in Muslim societies, compared to their secular counterparts, Islamic women have not taken an extensive part in the discourse of women‘s rights and feminism. In light of this perception, this paper will highlight Islam‘s gender egalitarian values and discuss the urgency and efficacy of Muslim women‘s greater involvement in the discourse of women‘s rights.